Qualification system as an instrument of personnel managementin Kazakhstan - V T Balgabayeva (RUDN Journal of Economics, 2011)
In the article the problems of development of professional standards for key industries of Kazakhstan and their interface with the system of vocational and technical education are considered. Analyzed the main features and benefits created by the National Professional Qualification System, which is the basis for the reform of vocational education in the country. The method of functional analysis as a phase definitions and descriptions of hierarchical levels of professional activity are considered. Justified, that the formation mechanisms for maintaining, updating and use of professional standards will support solving problems of staff policy and staff management.